Outcome of Penetrating Brain Injury in Civilian Practice - Malav, Ram Avatar; Ojha, Bal Krishna; Chandra, Anil; Singh, Sunil K.; Srivastava, Chhitij; Chandra, Nagesh; Srivastava, Saurabh; Gupta, Amit (Indian Journal of Neurotrauma, 2015)
Introduction There is a dramatic increase in the incidence and little is known about outcome and recovery of penetrating brain injuries. Our study is based on analysis of clinical-radiological profile and outcome of patients of penetrating brain injuries.Method This is a retrospective analysis of patients with penetrating head injury during the period from June 2004 to May 2013. Patients with penetrating head injury were selected from our hospital record. Their operative findings were evaluated and only those patients with documented penetration of the dura by a foreign material were selected for data collection and analysis.Results A total of 60 patients were recruited in the study. Their mean age was 27 years, and most patients were male. Most common clinical presentation was brain matter and cerebrospinal fluid (CSF) leak in 48 (60%) patients followed by decreased level of consciousness in 40 (66.67%) patients. Frontal lobe was most commonly involved part in 24 (40%) patients followed by multiple lobe injury noted in 16 (26.66%) patients. Twelve patients expired during the hospital stay. Thirteen patients were discharged in GOS-2, 15 in GOS-3, and 20 in GOS-4. Wound infection occurred in 11 (18.33%) patients, and seizure developed in 8 (13.33%) patients.Conclusion Penetrating brain injuries are most common in 11- to 30-year-old age group and occur more commonly in male. Most common presentations were brain matter or CSF leak and most common mode of injury was firearm. Frontal lobe was the most commonly injured part of the brain and mortality was 20%. Higher mortality was observed among patients with seizure than in other patients with penetrating brain injury.
Keywords: penetrating; civilian; head injury